(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
The development of technology shows the innovation of increasing progress in human life over time. Artificial Intelligence (AI) is one of the smart creations that change a process from various angles in the industry. However, the passage of time now shows that the advancement of this technology is actively applied in our society when we want to know the law or fatwa of a matter even though it is very beneficial and good. Therefore, this study aims to discuss the concept of artificial intelligence (AI) application according to Islamic perspective. In addition, Examining the effectiveness of artificial intelligence can determine certain fatwa issues and identify the Shariah guidelines in applying artificial intelligence (AI) on fatwa issuance. This study is a qualitative method that collects all information from various reading reference mediums. Furthermore, this study found that there is no authentic source from AI issuing new fatwa issues apart from Muslim scholar experts such as Mufti who are more knowledgeable and have good procedures in setting fatwas according to Islamic Shariah. The suggestion for improvement is to produce guidelines to follow Shariah so that its use is not excessive and avoid the risks that will occur.